Digitalization among Refugees in Malaysia - Mohd Ramlan Mohd Arshad; Mohd Na’eim Ajis (Proceedings, 2022)
There are issues with connectivity and networking for refugees during their stay in Malaysia. Thus, this study aims to examine digitalization activities among refugees. This qualitative study with purposive sampling involved three informants representing the government, private sector, and NGOs based in Putrajaya, Malaysia. The conducted analysis found that a digitization process has taken place, but related parties must ensure digital systems function evenly when addressing the refugee problem in Malaysia. The results could benefit the government and other parties directly involved in refugee issues such as the UNHCR, local NGOs, the private sector, and civil societies.